Revisiting revenge tragedy new perspectives - Hansen, Adam; Prandoni, Marco 1978-; Haven, Cornelis van der 1978- (Brill, 2025)
"Revisiting Revenge Tragedy explores one of the most popular and influential genres of early modern theatre. Revenge tragedies resonated with audiences and authors because of their explicit and often horrific depictions of political instability, religious violence, and affective distress. In innovative and provocative ways, this book situates the political, religious, and affective dimensions of such plays within the transnational dynamics of their inception and dissemination across a conflicted Europe, raising questions for us now about authority, tyranny, and justice. Moreover, detailed case studies demonstrate how depicting revenge questioned or evinced sometimes radical sexual, cultural, and political identities and positions"--
Keywords: Theater; Tragödie; European drama (Tragedy) / History and criticism; Tragedy / History and criticism / Early works to 1800; Theater / Europe / History / 17th century; Theater and society / Europe / History / 17th century; Revenge / Drama; Tragédie européenne / Histoire et critique; Tragédie / Histoire et critique / Ouvrages avant 1800; Théâtre / Europe / Histoire / 17e siècle; Théâtre et société / Europe / Histoire / 17e siècle